O ensino da Clínica Ampliada na Atenção Primária à Saúde: a prática de professores tutores e alunos de graduação médica - Godoy, Daniele Cristina (2018)
The contemporaneous crisis in the medicine and the challenges to the medical education have been issue for a huge international debate in the last decades. Among those challenges, there are some highlights: practice dehumanization, the individual health care fragmentation and the inequality of access to health care. In the light of this context, it has been recommended several measures to change medical training, in order to overcome such problems, among which, a closer approximation of this training with the public health systems. The structuring of the Unified Health System (SUS) in Brazil, although late, has been producing a new reorientation schedule of professional training from programs of Ministry of Health and Education, of incentives to change the graduations of the health professions. The Faculty of Medicine of Botucatu (FMB), with a long history of medical education in the community has been participating of the before mentioned programs of incentive to the restructuring of medical education. Within this scope of changes, the University-Services-Community Interaction Program (IUSC) was created in 2003. In its development, it was structured like a set of disciplines directed to undergraduation in medicine and nursing, having as teachinglearning scenario the territory, public facilities, especially basic health units, and community institutions. The practices of these disciplines are developed guided by the problematization methodology and by the conceptions of the practice humanization and the integrality of care. This study took as a field the discipline IUSC III, given to the students of the 3rd year of medical undergraduation, whose main activity is supervised medical consultation and guided by the design of the "Expanded Clinic". To achieve its goal of "developing skills and abilities to care for and promote community health" IUSC III has as pedagogical strategies: the longitudinal link, the use of the "extended anamnesis" script, case discussions with different health professionals and the use of field diaries. This research proposes to recognize the practice of professors and students in the teaching-learning process of the Expanded Clinic in Primary Health Care, through an ethnographic study of the daily life of this discipline. The field was developed during 14 months by means of bibliographical and documentary study and participant observation with record in field diary of the following moments: introduction module, observation activity and health unit recognition by the students, supervised medical consultation, case discussion meetings, clinical supervision and coordination meetings of the discipline with the professors. From the analysis of the field diaries and the documentary and bibliographic study of IUSC III pedagogical strategies, a dense description of his daily life was elaborated through dialogue with the framework of the Expanded Clinic and studies of the medical and clinical work. The study shows the power of pedagogical strategies for the development of a broader student’s view about the health needs of the users. Besides the significant receptivity of the students to a discipline of clinical practice in which the student has an active role already in the third year, part of them are resistant to the production of narratives from clinical encounters. The clinical experience in primary care is challenging for students, faced with a demand that is placed on a border between the problems of life and the well-defined diagnosis, Abstract which adds to the ambiguity and uncertainty of knowledge itself and medical practice. The analysis of this experience of students and professors with the teaching of the Expanded Clinic in Primary Health Care, although takes just a little space in the curriculum, it is fertile for reflection on medical teaching and possible paths and strategies for graduation change.